Embryo culture conditions are significantly improved during uninterrupted incubation: A randomized controlled trial - Alhelou, Yousef; Mat Adenan, Noor Azmi; Ali, Jaffar (Elsevier, 2018)
A parallel group superiority prospective randomised controlled trial was devised to compare the culture characteristics of human pre-implantation stage embryos during uninterrupted culture in a time lapse incubator (TLI) versus the conventional model of interrupted culture in a standard incubator (SI) under low oxygen tension using a single step medium. 221 patients aged 35-and-under, 124 patients aged between 36 and 39 and 86 patients aged 40-and-over years were randomised and cultured either in a SI or in a TLI. Patients in the three age groups were distributed between the TLI and SI in a 1:1 ratio. The development of embryos on days 2, 3 and 5, and the clinical pregnancy and implantation rates were recorded. The fertilisation rate, development of day 2 and clinical pregnancy rates were similar in both treatments but the 8-cell development rate in all age groups combined (p = 0.016), blastocyst development rate (p = 0.0022) and the implantation rate (p = 0.0022) was significantly higher for the uninterrupted culture. These findings demonstrated significant differences between the two incubation groups. It also indicated less efficacious embryonic development with age in both treatments which appeared more pronounced in the conventional incubator. In conclusion uninterrupted culture is superior compared to the interrupted incubation culture system.